Nonlinear seismic response of the bridge pile foundation with elevated and embedded caps in frozen soils. Issue 161 (October 2022) - Zhang, Xiyin; Yu, Shengsheng; Wang, Wanping; Guan, Jiada; Xu, Zhengjiang; Chen, Xingchong
Abstract: For pile group foundations used in cold regions with frequent seismic activity, the pile cap embedment conditions and freezing-thawing effect of soil layer deserve concerns in seismic design. In this study, quasi-static tests are carried out to investigate seismic failure characteristics of the bridge pile foundation with elevated and embedded caps in frozen soils. It is found that there is a big difference of the mechanical behavior and failure characteristics between the bridge pile foundation with embedded and elevated caps under cyclic lateral loading. Meanwhile, an improved nonlinear analysis model of the pile-soil interaction (PSI) system considering frozen soil effect is established and validated by experimental results. Furthermore, nonlinear seismic responses of the bridge pile foundation with different cap embedment conditions are furtherly explored. Compared with the bridge pile foundation with elevated cap, the embedded cap is beneficial to the pile foundation but adverse to the bridge pier under seismic actions. Experimental and numerical results indicate that the bridge pile foundation with embedded cap can lead to severe damage to the bridge pier if earthquake occurs. The strong constraint of frozen soil layer on the pile foundation can effectively reduce the lateral displacement of the bridge pier with pile foundations. The nonlinearity of upper layer soil in unfrozen condition is stronger, and the residual displacement is larger than that in frozen condition. These results can provide reference guide for seismic design of bridge pile foundation in frozen soils. Highlights: Quasi-static test of pile foundation with elevated and embedded caps are conducted. An improved analysis model of the pile-frozen soil interaction system is established. Effect of pile cap embedment conditions on seismic response of the pile is analyzed. Time-history analysis of the PSI system considering frozen soil effect is conducted. Nonlinear characteristics of the PSI system under seismic actions are discussed.